The 'Hungry Gap': Twitter, local press reporting and urban agriculture activism. Issue 6 (2nd December 2018) - Reed, Matt; Keech, Daniel
Abstract: This paper is concerned with how urban food activists related to the media during 2015, when Bristol was the European Green Capital (EGC), how they represented themselves and how others represented their agenda. Our intention is to inform the debates on urban agriculture (UA) and, more specifically, to contribute to discussions about 'scaling up' UA. To achieve this, we adopt a form of analysis that rests on Castells' insights about contemporary protest movements, the media and the role of communication technologies in constituting social power. By using Bristol, a city with a well-developed and studied urban agriculture movement, we suggest new areas for consideration that focus on the importance of communication in the development of the movement. Our study relied only on publicly available data; newspaper reports about the EGC and a sample of the social media used by the urban food networks in the city. We found that the mass media was mainly concerned with reporting topics other than food and that urban food was not a salient issue in their coverage. The Twitter network we analyzed was a loose constellation of different communities, which shared materials that were mostly concerned with creating a shared, normative picture of urban food. By considering the structure of these forms of media, we can observe the assembly of the forms of communication and their content. The paper concludes that the self-representation of urban food networks at that time reveals a narrow focus of interest. This emphasis may have contributed to the lack of connection within the city between potential allies. Our conclusion supports similar research findings in neighboring communities, which have observed the limited connections of urban food networks to the circuits of power and influence.